Family Support in Enhancing the Independence of Children with Intellectual Disabilities in Daily Living Activities - Eka Nurwahyuliningsih, Eka Nurwahyuliningsih; Djulaiha Sukmana, Djulaiha Sukmana; Faisyahril, Ria (Rumah Jurnal, University of Jember, 2025)
This study aims to determine the role of family support in increasing the independence of children with disabilities in carrying out daily activities. This study uses qualitative methods as a research approach with research subjects, namely four families who have children with disabilities, so the technique of selecting informants uses purposive sampling. Data were collected through non-participant observation, in-depth interviews, and documentation studies. Data analysis techniques used data reduction, data collection and conclusion drawing. The results showed that family support is crucial in increasing the independence of children with disabilities. The family is the first person to be present and accept the child's condition as a whole. The forms of support include informational support by providing advice and information to children so that they can carry out various activities on their own but are still accompanied; recognition support, which gives appreciation to children when children successfully complete a basic job well; instrumental support, which provides complete facilities such as therapy and skills training; emotional support, which is concerned with concern, sympathy and empathy, acceptance, and affection from the family to children. These forms of support contribute to improving children's ability to carry out daily activities independently. In addition, the importance of synergy between family and social environment in shaping children's independence in a sustainable manner.